DIGITAL FINANCIAL LITERACY AND ITS EFFECT ON PERSONAL FINANCIAL PLANNING IN THE CASHLESS SOCIETY - Billy Dewantara; Andi Primafira Bumandava Eka; Masyaili Masyaili (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This study aims to analyze the effect of digital financial literacy on personal financial planning in the context of a cashless society. The research employs a qualitative approach using a literature review method, examining various scholarly sources such as journal articles, books, and institutional reports relevant to the topic. The findings indicate that digital financial literacy is a critical factor influencing individual financial behavior, particularly in budgeting, saving, investing, and debt management. In digital payment systems, individuals tend to experience reduced awareness of spending due to the diminished “pain of paying,” which may lead to increased consumptive behavior. However, individuals with higher levels of digital financial literacy are better able to manage their finances effectively and maintain financial stability. Furthermore, digital financial literacy plays an essential role in mitigating financial risks, including fraud and cybersecurity threats. This study highlights the importance of enhancing digital financial literacy to support sustainable personal financial planning in an increasingly digitalized financial environment.